2019
DOI: 10.1182/blood.2018891192
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic high-throughput sequencing of 2396 patients with bleeding, thrombotic, and platelet disorders

Abstract: This paper reports on the use of a high-throughput diagnostic genetic screening for coagulation, platelet, or thrombotic disorders in a series of more than 2000 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
211
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(241 citation statements)
references
References 47 publications
11
211
1
2
Order By: Relevance
“…37 Recently, it has been shown that ThromboGenomics gives a diagnosis for a UBD in only 3.2% cases tested in a large cohort of patients (although these were not clearly patients with UBD). 38 This study and the normal ThromboGenomics in our cohort (45 patients) suggest further genetic research is required to establish the genetic basis of UBD.…”
Section: Discussionmentioning
confidence: 82%
“…37 Recently, it has been shown that ThromboGenomics gives a diagnosis for a UBD in only 3.2% cases tested in a large cohort of patients (although these were not clearly patients with UBD). 38 This study and the normal ThromboGenomics in our cohort (45 patients) suggest further genetic research is required to establish the genetic basis of UBD.…”
Section: Discussionmentioning
confidence: 82%
“…In our study, 25 patients remain undiagnosed despite their clinical presentation with thrombocytopenia or a clinically relevant bleeding score. Even larger studies, like the recently published study by Downes et al including 2396 patients could only show a rate of 3.2% for patients with unexplained bleeding disorders characterized by normal haemostasis test results . These patients may have acquired diseases or variants in unknown genes or regulatory regions.…”
Section: Discussionmentioning
confidence: 84%
“…All class 4 and 5 variants were found in children with thrombocytopenia, and directed functional testing was able to confirm the genetic findings. The overall diagnostic rate 27 and our own previously published adult cohort (n = 156),…”
Section: Significant Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…6 Cosegregation studies would support the genotype-phenotype correlation for our cases; however, we did not have access to samples from pedigrees. Concerning the possibility of other factors underlying the macrothrombocytopenia, it should be noted that all genes currently known for macrothrombocytopenia were evaluated in our patients using the ThromboGenomics gene panel test 5 and no other variants were found that could modify the phenotype.…”
Section: Letter To the Editormentioning
confidence: 99%